Social Integration and Isolation: Examining the Impact of Elderly Attitudes on Community Engagement and Well-Being (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The general well-being of the elderly might be negatively impacted by feelings of loneliness and social isolation. This study looks at the mediating roles of gender, marital status, and education level in the relationship between social isolation and loneliness and the psychological well-being of older adults living in different old-age homes in India. The sample size is 320 people, all of whom are 60 years old or older. Ryff and Keyes's shorter version of the psychological well-being scale, the UCLA Loneliness Scale, and the Lubben Social Network Scale–6 were among the standardised measures used for data collection (1995). In order to comprehend the relationships between psychological health and social isolation or loneliness, researchers used multivariate and mediation analysis. Both social isolation (F = 3.836, p